Study of the Effect of Europium Acetate on the Intermolecular Properties of Water - Slatinskaya, O. V.; Pyrkov, Yu. N.; Filatova, S. A.; Guryev, D. A.; Penkov, N. V. (Frontiers in Physics, 2021)
In this work, the effects of europium acetate and intensive stirring on the intermolecular properties of water in solutions were investigated. To do this, we studied aqueous solutions of europium acetate in a wide range of concentrations, which were prepared by the method of serial dilutions using a microfluidic unit. Water and similarly prepared water dilutions were used as controls. Raman spectroscopy and infrared (IR) spectroscopy were applied to assess the features of hydrogen bonds formed in the studied solutions. Using Raman spectroscopy, it was shown that intermolecular binding is stronger in solutions of europium acetate of 10-1 M and 10-3 M than in water controls. On the contrary, solutions of europium acetate at a concentration of 10-10 М and some lower concentrations demonstrate weaker hydrogen bonding than in the respective water dilutions, which was shown by the both methods. Such differences were observed even in those solutions where the calculated concentration of europium acetate was below 10-24 M. When comparing water with control dilutions of water, it was established that intermolecular binding is different (stronger or weaker) in high dilutions of water than in water not subjected to the dilution procedure. This indicates a significant influence of the dilution process itself on the properties of water in solutions. Apart from that, the paper discusses the energy state of water molecules in the studied solutions.